2008
DOI: 10.1155/2008/370947
|View full text |Cite
|
Sign up to set email alerts
|

Penile Corporeal Reconstruction during Difficult Placement of a Penile Prosthesis

Abstract: For some patients with impotence and concomitant severe tunical/corporeal tissue fibrosis, insertion of a penile prosthesis is the only option to restore erectile function. Closing the tunica over an inflatable penile prosthesis in these patients can be challenging. We review our previous study which included 15 patients with severe corporeal or tunical fibrosis who underwent corporeal reconstruction with autologous rectus fascia to allow placement of an inflatable penile prosthesis. At a mean follow-up of 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Penile prosthesis implantation in patients with severe fibrosis of the corpora cavernosa still repre- sents a challenge and is associated with low levels of patients' satisfaction because of penile shortening and elevated rate of intra-and postoperative complications [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penile prosthesis implantation in patients with severe fibrosis of the corpora cavernosa still repre- sents a challenge and is associated with low levels of patients' satisfaction because of penile shortening and elevated rate of intra-and postoperative complications [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive corporotomies or distal second incisions, excision of the scarred tissue, and the use of the Otis urethrotome, cavernotomes, and resectoscope loops has shown to be useful to create sufficient space to house the cylinders in the vast majority of patients. However, in some cases, the degree of scarring and contracture is so severe that closure of the tunica albuginea over a penile implant is impossible, and therefore reconstruction of the corpora with a patch becomes necessary [1,2,[7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…With extensive corporal fibrosis, a penile implant is the only viable option to alleviate sexual dysfunction [16] . In cases of scarred penile corporal bodies, the surgery becomes challenging even for experienced surgeons, as it can be extremely difficult or indeed impossible to dilate the corpora [3,17,18] .…”
Section: Penile Prosthesis Implantationmentioning
confidence: 99%
“…Patients presenting with severely contracted corpora cavernosa following repeated explantation of infected penile prosthesis should instead be offered simultaneous total corporeal reconstruction and penile prosthesis implantation as this technique yields good results in expert hands. 21 This procedure is indicated only if the contracture of the tunica albuginea is so severe that, after adequate dilatation of the corpora, the corporotomies cannot be closed even on downsized cylinders. In particular, in a series of eight patients managed with simultaneous total corporeal reconstruction with the use of rectus fascia graft and penile prosthesis implantation, Patak et al 21 reported no complication after a median follow-up of 18 months (Figure 2).…”
Section: Scrotal Reconstructionmentioning
confidence: 99%
“…21 This procedure is indicated only if the contracture of the tunica albuginea is so severe that, after adequate dilatation of the corpora, the corporotomies cannot be closed even on downsized cylinders. In particular, in a series of eight patients managed with simultaneous total corporeal reconstruction with the use of rectus fascia graft and penile prosthesis implantation, Patak et al 21 reported no complication after a median follow-up of 18 months (Figure 2).…”
Section: Scrotal Reconstructionmentioning
confidence: 99%